2020
DOI: 10.3390/plants9020264
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Inhibitory Activities and Volatile Active Compounds of 53 Spices and Herbs

Abstract: The inhibitory activities of the leachates and volatiles from 53 plant species (spices and herbs) were evaluated against lettuce (Lactuca sativa “Great Lakes 366”) seedling growth using the sandwich and dish pack methods, respectively. With the sandwich method, parsley (Petroselinum sativum) showed the strongest inhibitory effect on lettuce radicle growth (77%), followed by tarragon (Artemisia dracunculus) (72%). However, caraway (Carum carvi), dill (Anethum graveolens) (seed), laurel (Laurus nobilis), rosemar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Both mint plants are herbaceous, with soft leaves that degrade rapidly [ 8 ], and contain similar amounts of essential oils, which do not differ greatly from each other qualitatively; in the essential oils of both plants, menthol and isomenthone are the major constituents ( Table 1 ). On the other hand, rosemary (Ro) is an evergreen shrub with hard, slowly degrading leaves that contain essential oils, which are rich in such plant-growth-inhibiting allelochemicals as cineol, camphor, and a-pinene [ 12 , 13 ], and persist for long durations in the soil environment [ 8 ]. As a result, the Ro amendment had a very strong negative impact on the growth of the tomato seedlings, contrary to the Ms and Mp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both mint plants are herbaceous, with soft leaves that degrade rapidly [ 8 ], and contain similar amounts of essential oils, which do not differ greatly from each other qualitatively; in the essential oils of both plants, menthol and isomenthone are the major constituents ( Table 1 ). On the other hand, rosemary (Ro) is an evergreen shrub with hard, slowly degrading leaves that contain essential oils, which are rich in such plant-growth-inhibiting allelochemicals as cineol, camphor, and a-pinene [ 12 , 13 ], and persist for long durations in the soil environment [ 8 ]. As a result, the Ro amendment had a very strong negative impact on the growth of the tomato seedlings, contrary to the Ms and Mp.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chalkos et al [ 10 ] showed that spearmint compost, when added at a rate of 4% to 8%, stimulated tomato growth, increased soil bacterial and fungal abundance, and inhibited weed emergence. On the other hand, spearmint essential oil and/or its constituents were found to inhibit seedling emergence and the growth of tomato, cotton, and several weeds [ 11 ], whereas the major essential-oil constituents of these three aromatic plants, including carvone, menthol, cineol, and camphor, were found to strongly inhibit both lettuce germination and seedling growth in laboratory experiments [ 12 , 13 ]. The essential oils of all three plants were also proven to be efficient against phytoparasitic nematodes [ 14 , 15 ], while improving through their root exudates the growth of infested sunflower plants [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…essential oil and its main compounds limonene (40.92%) and citral (27.46%) facing three important monocot weeds: Avena fatua L., Phalaris minor Retz. and Echinochloa crus-galli (L.) Beauv., demonstrated the low phytotoxicity of the hydrocarbon monoterpene with respect to the whole essential oil and the oxygenated monoterpene [68], corroborating the fact that monoterpene hydrocarbons usually exhibit less potent allelopathic activity than oxygenated ones [67][68][69][70][71][72][73].…”
Section: Herbicidal Activitymentioning
confidence: 56%
“…The leaf extract of rosemary was reported to be potentially phytotoxic, and carnosic acid was reported as an allelochemical in the leaves of the plants [ 34 ]. Rosemary leaves also contain volatiles such as 1,8-cineole, which showed inhibitory effects on lettuce growth [ 35 ]. Carnosic acid has only been identified in a few plant species, all of which belong to the Lamiaceae family [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%